An aminotetracyanocyclopentadienide system: light-induced formation of a thermally stable cyclopentadienyl radical. (3rd December 2019) - Nimax, Patrick R.; Zoller, Florian; Blockhaus, Tobias; Küblböck, Teresa; Fattakhova-Rohlfing, Dina; Sünkel, Karlheinz
Abstract : Crystals of the aminotetracyanocyclopentadienyl radical were obtained from the reaction of CaCl2 with Ag[C5 (CN)4 (NH2 )] and recrystallization in MeOH was performed in sunlight. Abstract : Crystals of the aminotetracyanocyclopentadienyl radical were obtained from the reaction of CaCl2 with Ag[C5 (CN)4 (NH2 )] and recrystallization in MeOH, performed in sunlight. The radical was characterized by X-ray diffraction, EPR and UV Vis spectroscopy as well as by cyclovoltammetry and DFT calculations.